1984
DOI: 10.1037/0735-7044.98.4.712
|View full text |Cite
|
Sign up to set email alerts
|

Maternal behavior in rats: Evidence for the involvement of preoptic projections to the ventral tegmental area.

Abstract: This study provides evidence that a neural system extending from the preoptic region to the ventral tegmental area (VTA) of the midbrain is important for the normal expression of maternal behavior in lactating rats. In the first experiment, bilateral electrolytic lesions of the VTA severely disrupted the maternal behavior of postpartum rats. In the second experiment, lactating rats that received a unilateral knife cut severing the lateral connections of the medial preoptic area (MPOA) paired with a contralater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
138
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(143 citation statements)
references
References 22 publications
3
138
0
1
Order By: Relevance
“…Results showing evidence of oxytocin receptor density in the accumbens has not been consistent (Tribollet et al, 1988; Veinante and Freund-Mercier, 1997), whereas its messenger RNA has not been clearly observed in this area (Yoshimura et al, 1993;Vaccari et al, 1998). Thus, it is possible that suckling and the effect of OT on neuronal activity in the accumbens, as suggested by the present data, may be mediated indirectly via the VTA and/or MPOA (Numan and Smith, 1984;Pedersen et al, 1994).…”
Section: Discussionmentioning
confidence: 50%
“…Results showing evidence of oxytocin receptor density in the accumbens has not been consistent (Tribollet et al, 1988; Veinante and Freund-Mercier, 1997), whereas its messenger RNA has not been clearly observed in this area (Yoshimura et al, 1993;Vaccari et al, 1998). Thus, it is possible that suckling and the effect of OT on neuronal activity in the accumbens, as suggested by the present data, may be mediated indirectly via the VTA and/or MPOA (Numan and Smith, 1984;Pedersen et al, 1994).…”
Section: Discussionmentioning
confidence: 50%
“…Electrolytic (Galfori and Le Moal, 1979;Numan and Smith, 1984) or 6-hydroxydopamine (Hansen et al, 1991(Hansen et al, , 1993 lesions of the VTA or the n. Acc greatly disrupt maternal behavior. Infusion of the mixed D 1 -D 2 receptor antagonist flupenthixol into the n. Acc significantly reduces pup LG (Keer and Stern, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The functional distinction between the role of the n. Acc shell and core is apparent in studies of stress responsivity (Kalivas and Duffy, 1995;Chretien et al, 1998), food reinforcement (Sokolowski et al, 1998), sexual behavior (Jenkins and Becker, 2001;Lopez and Ettenberg, 2002), and maternal behavior (Keer and Stern, 1999;Li and Fleming, 2003). The n. Acc shell receives both direct and indirect connections from the MPOA via the VTA (Simon et al, 1979;Numan and Smith, 1984;Zahm and Heimer, 1993). Knife cuts severing the lateral projections from the MPOA to the VTA seriously disrupt maternal behavior (Numan and Smith, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction would be what we have called an interaction between a specific and a nonspecific system. One piece of supportive evidence comes from study by Numan and Smith (1984), who showed that bilateral damage to a neural system which extends from the MPOA to the VTA disrupts maternal behavior in postpartum rats. Recall that bilateral lesions are necessary to severely disrupt maternal behavior.…”
Section: Mpoa Interactions With the Mesolimbic Da System And Maternalmentioning
confidence: 99%